2020
DOI: 10.1136/bmjopen-2019-035651
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer awareness and its predictors among adults aged 50–74 years attending primary healthcare in the State of Qatar: a cross-sectional study

Abstract: ObjectiveThe current study aimed to assess the awareness of colorectal cancer (CRC) symptoms and risk factors among the at-risk population visiting the primary healthcare (PHC) centres in Qatar. The secondary objective was to assess the differences in awareness among population subgroups.DesignA cross-sectional study design was employed.Setting Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 12 publications
(11 reference statements)
7
17
0
Order By: Relevance
“…In concordance with this study, previous studies reported low levels of CRC awareness in other Arab countries including Lebanon (33% displayed good awareness), Jordan (34.5%), Qatar (40.2%), and United Arab Emirates (< 50.0%) [ 43 46 ]. Conversely, studies in non-Arab countries showed better CRC awareness: the United States of America (91.0% showed good awareness), the United Kingdom (88.0%) Malaysia (70.9%), Turkey (69.0%), and Norway (60.0%) [ 47 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…In concordance with this study, previous studies reported low levels of CRC awareness in other Arab countries including Lebanon (33% displayed good awareness), Jordan (34.5%), Qatar (40.2%), and United Arab Emirates (< 50.0%) [ 43 46 ]. Conversely, studies in non-Arab countries showed better CRC awareness: the United States of America (91.0% showed good awareness), the United Kingdom (88.0%) Malaysia (70.9%), Turkey (69.0%), and Norway (60.0%) [ 47 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…43 Despite several diabetes campaigns in Palestine, 44 having diabetes was the least recognized nonmodifiable risk factor, as also in Qatar, Ethiopia, and the United Kingdom. 12,[45][46][47] Therefore, awareness campaigns should focus more on the long-term consequences of diabetes including the potential to develop CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The higher level of awareness among women in this study is consistent with previous studies. 10,45,48 This might be attributed to the fact that women use health care services more often (eg, for maternity care) than men and, thus, come in contact with health care providers more frequently. Therefore, women might have more opportunities to gain information from health care providers on health-related topics, including CRC, which might motivate them to adopt more protective behaviors than men.…”
Section: Discussionmentioning
confidence: 99%
“…The system based barriers include lack of resources, disintegrated medical systems and lack of test recommendation to patient by the treating physicians. Patients based barriers include unawareness of symptoms and risk factors of CRC, lack of knowledge of screening tests and their significance, embarrassment from doing the test and stigma about being diagnosed with cancer [4,[24][25][26][27][28][29][30]. A study from UAE reported that almost 95% of participants were not advised to do the CRC screening by their physicians [31].…”
Section: Status Of Crc Screening In the Arab Region And Barriers To I...mentioning
confidence: 99%